The Use of Context Clues Technique on Students’ Reading Comprehension at Senior High School - Safika, Nurul; Fauzana, Riri (State Islamic University of Sultan Syarif Kasim Riau, 2023)
The objectives of the research were to investigate the students` reading comprehension of narrative text taught without using the Context Clues technique, to investigate the students` reading comprehension of narrative text taught by using the Context clues technique, and to determine whether there is a significant difference in the improvement of students` reading comprehension taught using Context Clues Technique and taught without Context Clues Technique at Islamic Senior High School Daarun Nahdhah Thawalib Bangkinang's tenth-grade students. The population of the research was the tenth-grade students of Islamic Senior High School Daarun Nahdhah Thawalib Bangkinang. The classes chosen as the sample were IV A, the experimental class, and IV C, the control class, each of which included 34 students. The researcher employed a pre-test and a post-test to collect data on the student's reading comprehension of narrative text in this research. In addition, there was a large effect of using the Context Clues technique on students` reading comprehension of the narrative text of the tenth-grade students at Islamic Senior High School Daarun Nahdhah Thawalib Bangkinang, the result of Eta Squared was 0.70.